Teaching English included questions to Bicolano in the high schools - Espinocilla, Hilda Escultura 1931- ([Quezon City s.n.], 1965)
This material for teaching involves questions based on a comparison between English and Bicol included questions. The instructional materials are directed towards the difficulty of Bicolano learners of English included questions.
Thesis (M.A.T.)--University of the Philippines
Keywords: English language -- Study and teaching